Pendidikan Robbaniyyah dalam Perspektif Al-Qur'an - Surasman, Otong (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2020)
How important it is in modern times to return mankind back to the right path, after most humans have taken many paths of life that are not true. As real proof is the loss of a good human personality according to the nature of origin, where humans are born in a state of pure holiness. Then how important it is to explore rabbaniyyah education again, so that humanity can still be able to live life in this world in accordance with the nature of humanity. Now, to achieve all this, there needs to be serious and disciplined efforts, so that by reestablishing the basic principles of life with rabbanuyah education will be realized, so as to create a life full of harmony, peace, peace and fulfillment of all the needs of life, that is enough clothing , food and shelter, and free from poverty and ignorance and discrimination. To achieve that all of them need clear and accurate solutions, then there is no other effort is to re-explore from the original source of Allah's guidance through the Holy Qur'an, which specifically explores rabbaniyyah education in the Qur'an. And more specific is to explore the verses of the Qur'an that are closely bound to humans as an-Nas (social beings), so that every human being will come to know himself as a human being.